2015
DOI: 10.1111/rda.12629
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Characterization of Zinc‐Binding Proteins of Canine Seminal Plasma

Abstract: The zinc-binding proteins (ZnBPs) of the seminal plasma are implicated in different processes related to sperm-egg fusion. The aim of this study was to characterize the ZnBPs of canine seminal plasma using two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and mass spectrometry. The ZnBPs were isolated from the ejaculates of five dogs by affinity chromatography and subjected to 2D-PAGE analysis. The acquired spots, detected across the gels, were analysed by mass spectrometry. Using 2D-PAGE analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Recently, it was suggested that the CPSE is secreted in the form of prostasomes (prostate granules) to semen during ejaculation. The activity of CPSE is regulated by the level of available zinc that is of great importance for maintaining the normal functions of the prostate and the spermatozoa (Mogielnicka-Brzozowska, Kowalska, Fraser, & Kordan, 2015). The production of CPSE is regulated by androgen hormone (testosterone); it can be inhibited by the surgical castration or antiandrogen treatment (Frenette, Dube, Marcotre, & Tremblay, 1983;Isaacs & Sharper, 1985;Juniewicz et al, 1990) or promoted by the exogenous androgen administration following the surgical castration (Frenette et al, 1983;Isaacs & Sharper, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that the CPSE is secreted in the form of prostasomes (prostate granules) to semen during ejaculation. The activity of CPSE is regulated by the level of available zinc that is of great importance for maintaining the normal functions of the prostate and the spermatozoa (Mogielnicka-Brzozowska, Kowalska, Fraser, & Kordan, 2015). The production of CPSE is regulated by androgen hormone (testosterone); it can be inhibited by the surgical castration or antiandrogen treatment (Frenette, Dube, Marcotre, & Tremblay, 1983;Isaacs & Sharper, 1985;Juniewicz et al, 1990) or promoted by the exogenous androgen administration following the surgical castration (Frenette et al, 1983;Isaacs & Sharper, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the epididymal spermatozoa do not show the enzyme (Isaacs & Coffey, 1984). As a sperm‐binding protein, the CPSE seems to be involved in events related to sperm fertilization (Mogielnicka‐Brzozowska, Kowalska, Fraser, & Kordan, 2015) and, given to its ability to bind to zinc ions, it turns out to be a multifunctional molecule (Acquino‐Cortez et al., 2017; Chapdelaine et al., 1984; Dube et al., 1986). Studies are warranted to better clarify the specific role of the CPSE in the fusion process between oocyte and spermatozoa (Mogielnicka‐Brzozowska, Sowinska, & Fraser, 2017).…”
Section: The Choice Of a Prostate Biomarker In Canine Andrologymentioning
confidence: 99%
“…There were positive correlations between two particular protein bands, B4 (67 kDa) and B5 (58.6 kDa), and sperm motility, sperm vigour, percentage of morphologically normal spermatozoa, the hypo‐osmotic swelling test and fluorescent staining. Using 2D‐PAGE analysis, it was shown that canine seminal plasma contains approximately 46–57 zinc‐binding polypeptides (Mogielnicka‐Brzozowska, Kowalska, Fraser, & Kordan, ). Their molecular mass ranging from 9.3 to 138.7 kDa.…”
Section: Review Of Sperm Functional Testsmentioning
confidence: 99%